Identification of the distribution of valuations in an incomplete model of English auctions - Andrew Chesher; Adam Rosen (Centre for Microdata Methods and Practice (cemmap), 2015)
An incomplete model of English auctions with symmetric independent private values, similar to the one studied in Haile and Tamer (2003), is shown to fall in the class of Generalized Instrumental Variable Models introduced in Chesher and Rosen (2014). A characterization of the sharp identi.ed set for the distribution of valuations is thereby obtained and shown to re.ne the bounds available until now.
Keywords: 330; English auctions; partial identification; sharp set identification; generalized instrumental variable models